38 Growing need, growing complexity: projections of palliative care need and multi-mortality in scotland. (13th October 2019) - Finucane, Anne; Bone, Anna; Etkind, Simon; Carr, David; Meade, Richard; Munoz-Arroyo, Rosalia; Moine, Sebastian; Murray, Scott; Iyayi-Igbinovia, Aghimien; Evans, Catherine; Higginson, Irene; Boyd, Kirsty
Abstract : Background: Due to population ageing, serious health related burden is rising. In England and Wales, the number of people requiring palliative care is projected to grow by 42% by 2040 (Etkind et al. 2017). We sought to estimate future palliative care need in Scotland, extending previous work by examining the contribution of multi-mortality (deaths from multiple conditions), to identify priorities for future service delivery. Methods: Simple linear modelling of deaths requiring palliative care from 2017–2040, using national death registry data (National Records of Scotland) and official mortality forecasts (Office of National Statistics). Palliative care need was estimated using previously defined chronic progressive illnesses, identified from i) leading cause of death; ii) contributory causes of death. Results: Using different methods, we projected that by 2040, the number and proportion of people requiring palliative care will increase, equating to between 75% (minimal estimate) and 94% (maximal estimate) of all deaths. Deaths due to >2 disease groups (cancer, organ failure, dementia, other) are projected to account for 42% of all deaths by 2040, up from 27% in 2017. Deaths due to dementia and cancer will increase. Most deaths will occur for those aged >85. If current trends continue, care complexity will rise. Conclusions: Estimates of palliative care need using leading and contributing causes of death demonstrate the complexity and extent of care needs. The forthcoming rise of palliative care need in Scotland requires strategic action to prepare, including greater palliative care training provision for generalist health professionals where people reside and receive care.